Development of a framework for assessing the economic benefit of remanufacturing - Jakpa, Onome, E. (Cranfield University, 2009)
Product waste is becoming a big problem in our life. In order to reduce waste and efficiently use resources, product can be remanufactured, and its materials can be recycled to achieve better sustainability. In comparison with recycling materials, remanufacturing products can retain all the value added, so potentially it has high profitability and sustainability. Despite its main advantage of retaining the value of the products, remanufacturing is an area that is not widely practiced due to the high costs of remanufacturing and reverse logistics facilities. As a result of this, the cost components had to be researched in order to ascertain the costs involved in the process of remanufacturing. The identification the cost drivers in each of the process provided the basis for a generic framework to be developed which gives remanufacturers a template to determine the economic benefits of remanufacturing from a whole systems point of view including the reverse logistics. Through the use of a specified methodology, this research aims to capture all the costs involved in the whole systems remanufacturing process given that the previous models that exist do not propose a costing model for both reverse logistics and remanufacturing. Ready to Use Additive Manufacturing – RUAM is a technique for creating robust three dimensional metal objects. It is application in the framework allows for the refabrication of EOL products.
Keywords: Product waste; remanufactured; recycled; sustainability; reverse logistics; Ready to Use Additive Manufacturing; RUAM